Les pratiques du gouvernement de soi à l’école : les dispositifs pédagogiques de l’autonomie et leurs contradictions - Héloïse Durler (Recherches en Éducation)
This contribution is based on an ethnographic survey in an elementary school in Geneva, bringing together observations in classes, interviews with teachers, observations in families and interviews with children and their parents. This survey highlights the inherent contradictions existing in dispositifs focusing on student autonomy. In this article, we will discuss the principles of socialization underlying these dispositives and how they express in the educational practices. We examine in particular their contradictory aspects.